Problem Solving pada Anak Usia Dini: Pemanfaatan Balok Sebagai Media Pembelajaran - Asmiaty, Asmiaty; Wahira, Wahira; Asrifan, Andi (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
This study aims to examine problem-solving abilities in early childhood through the use of geometric block media at TK Islam Athirah Bukit Baruga. Problem-solving ability is an essential cognitive skill that needs to be developed from an early age through meaningful learning experiences, one of which is play-based activities. Geometric block media were selected because they are constructive in nature and allow children to explore shapes, plan, try various strategies, and find solutions to problems that arise during play activities. This study employed a descriptive qualitative approach. The research subjects were children in Group B at TK Islam Athirah Bukit Baruga, with classroom teachers serving as supporting informants. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source, technique, and time triangulation. The results indicate that the implementation of geometric block media was carried out through the stages of play environment preparation, pre-play activities, during-play activities, and post-play activities. These stages created a conducive play environment and stimulated children’s problem-solving abilities. Children demonstrated the ability to identify simple problems, try various problem-solving strategies, and evaluate outcomes through block play experiences. Social interaction during play also contributed to the development of children’s thinking skills. These findings are consistent with Piaget’s and Vygotsky’s theories, which emphasize the importance of concrete experiences and social interaction in children’s cognitive development.